Competence investigation on insulation testing on electrosurgical instruments and needs analysis of training for Central Sterile Supply Department staff - Xu WANG; Qing ZHANG; Yi-Qin ZHOU (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this article is to investigate the competence of Central Sterile Supply Department (CSSD) staff in insulation testing on electrosurgical instruments, to analyze the needs of training for CSSD staff, and also to strengthen the effectiveness of monitoring the insulation testing on electrosurgical instruments for CSSD staff to provide a reference for the nursing safety training. Materials and Methods: A total of 180 CSSD staff from 36 hospitals were enrolled as the research objects and investigated using "self-assessment questionnaire of the competence in insulation testing on electrosurgical instruments and the needs of training". Results: The overall self-assessment score of competence in insulation testing on electrosurgical instruments for CSSD staff is 3.10 ± 0.42, including four dimensions which are attitude, system, cognition, and skills with the scores 3.31 ± 0.55, 2.80 ± 0.63, 2.74 ± 0.68, and 3.03 ± 0.36, respectively. Based on the survey of training needs for CSSD staff, the top three ranked training needs are trace management record of insulation testing on electrosurgical instruments (93.89%), disposal procedures for insulation damage of electrosurgical instruments (92.78%), and adverse events caused by leakage of electrosurgical instruments (80.55%). Conclusion: The competence of insulation testing for CSSD staff is at a low level by overall. The competence of CSSD staff could be improved by analyzing the needs of training, establishing a systematic training system, and taking effective training action, thus ensuring the safety of patients and medical personnel.